BEBERAPA FAKTOR TERJADINYA PERSALINAN SECTIO CAESAREA - Sugiarti Sugiarti (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
Sectio Caesarea is an artificial labor, in which the fetus is born through an incision in the abdominal wall and uterine wall on the condition that the condition is intact and the fetus weighs above 500 grams. Labor with Sectio Caesarea is based on the indication of the mother and fetus. At the Hospital DKT Gubeng Pojok Surabaya the 2015 incidence of Sectio Caesarea labor was 1003 people (80%) from the normal labor rate. Objective: This study aims to determine several factors in the occurrence of Sectio Caesarea labor in the DKT Hospital of Gubeng Pojok Surabaya in 2016. Method: This study used a descriptive design, the population of Sectio Caesarea mothers in 2016 was 534 people. Sampling using Systematic Random Sampling with a sample of some Sectio Caesarea delivery mothers in 2016 as many as 174 people. The instrument in this study used secondary data from the registration of maternity mothers and then processed using frequency tabulation and cross tabulation. Results: The results of the study showed that the majority of Sectio Caesarean mothers with primipara parity (55.17%) and work (64.94%). Based on age, Sectio Caesarea indications occur in mothers aged> 35 years (1.15%), past labor history with Caesarean section (32.76%), premature rupture of membranes (14.37%), at the request of the mother herself (31 , 03%), large infants (3.45%), abnormalities of fetal location (13.22%) and fetal distress (3.45%). Conclusions: the majority of Sectio Caesarea events occur in mothers with a previous history of labor. Therefore, it is expected that mothers before pregnancy or during pregnancy regularly check their pregnancy according to the standard, namely a minimum of 4x visits, counseling in the antenatal class accompanied by a husband, participating in pregnancy exercises and orientation in the maternity room so that the mother is ready to face childbirth.